Erosive discovertebral lesion (Andersson lesion) as the first sign of disease in axial psoriatic arthritis. (May 2013) - Queiro, R; Tejón, P; Alonso, S; Alperi, M; Ballina, J
Abstract : Objectives: To present two cases of Andersson lesion (AL) as the form of onset of psoriatic arthritis (PsA), to review the form of onset of axial disease in PsA in our area, and to study the prevalence of AL in this series. Patients and methods: Two patients with psoriasis and recent-onset inflammatory back pain (IBP) with no known arthritis are presented. A final diagnosis of AL based on magnetic resonance imaging (MRI) findings was made. The medical records of 120 consecutive patients with axial PsA were reviewed and the most relevant features at disease onset analysed. Results: Including the two cases presented, an AL prevalence of 5.7% was found in this series. The most common onset forms of axial PsA were: oligoarthritis (30%), IBP (21.7%), enthesitis (17.5%), polyarthritis (16%), gluteal pain (8.3%), dactylitis (3.3%), and distal interphalangeal (DIP) involvement (3.3%). Compared to women, men more frequently showed enthesitis (25% vs. 9%, p = 0.03) and IBP (31% vs. 10.7%, p = 0.007) as onset forms whereas a polyarticular onset was predominant in women (25% vs. 8%, p = 0.01). The polyarticular onset was predictive of radiological damage in the cervical column during follow-up [odds ratio (OR) 2.6, 95% confidence interval (CI) 1.82–6.83, p = 0.01]. Enthesitis (23.6% vs. 8.3%, p = 0.02) and IBP (29.7% vs. 10.4%) were the predominant onset forms in patients with age at disease onset ≤ 40 years and polyarthritis (27% vs. 8.3%, p = 0.009) was predominant in those with disease onset > 40 years. Conclusions: AL is an uncommon finding in axial PsA and its appearance at disease onset is exceptional. MRI is a key tool in its early recognition.